Concurrent staphylococcal and herpes simplex infections – diagnostic pitfalls. A case report - Walas, Wojciech; Halaba, Zenon P. (Pediatria Polska - Polish Journal of Paediatrics, 2018)
We describe the case of a six-year-old boy with concurrent staphylococcal septicaemia, herpes simplex virus encephalitis (HSVE), and haemorrhagic erosive oesophagitis. Due to guiding clinical and lab symptoms that suggested a diagnosis of staphylococcal sepsis with central nervous system (CNS) involvement, acyclovir treatment was discontinued after three days, but the lack of progress in neurological status, further lab tests, and CT and MRI imaging led the authors to consider possible HSV infection, and this diagnosis was confirmed by PCR test. Even though the treatment for HSV was applied again, the long gap in acyclovir medication contributed to a severe neurological deficit and an adverse outcome. Our case strongly suggests the need to consider HSV aetiology in making a differential diagnosis where there is an atypical course of a disease, even though clinical symptoms and lab results dictate another aetiology and continuing acyclovir supply until HSV aetiology is ruled out.